De la Grammatologie - Derrida, Jacques 1930-2004 (Paris Édtions de Minuit, 1967)
The book, originating the idea of deconstruction, proposes that throughout continental philosophy, especially as philosophers engaged with linguistic and semiotic ideas, writing has been erroneously considered as derivative from speech, making it a "fall" from the real "full presence" of speech and the independent act of writing.
Derrida discusses writers such as Claude Lévi-Strauss, Ferdinand de Saussure, Jean-Jacques Rousseau, Étienne Condillac, Louis Hjelmslev, Martin Heidegger, Edmund Husserl, Roman Jakobson, Gottfried Wilhelm Leibniz, André Leroi-Gourhan, and William Warburton. In the course of the work he deconstructs the philosophies of language and the act of writing given by these authors, identifying what he calls phonocentrism, and showing the myriad aporias and ellipses to which this leads them. Derrida avoids describing what he is theorizing as a critique of the work of these thinkers, but he nevertheless calls for a new science of "grammatology" that would explore the questions that he raises about how to theorize the act of writing.Of Grammatology introduced many of the concepts which Derrida would employ in later work, especially in relation to linguistics and writing.
Bibliographical footnotes.
Keywords: Philosophy; Linguistics